PerceptionGuard: Privacy-Aware Split Inference for Multimodal Mobile Applications - Sridhar Muthineni (Politeknik Negeri Batam, 2026)
Multimodal mobile AI applications increasingly rely on cloud-based large language models (LLMs) for complex reasoning over visual inputs, but raw-image cloud upload creates substantial privacy exposure, high inference costs, and unacceptable latency for interactive use cases. This paper proposes PerceptionGuard, a four-layer split-inference architecture where on-device vision-language models (VLMs) handle privacy-sensitive perception and adaptive routing, sending only compact, privacy-preserving representations to cloud LLMs for higher-order reasoning. Three representation modes are defined and evaluated: dense embeddings (Mode A), structured scene graphs (Mode B), and redacted natural-language captions (Mode C). The architecture incorporates information-bottleneck filtering and calibrated differential-privacy noise to resist membership inference and embedding-inversion attacks. Experimental evaluation across three representative mobile workloads, accessibility visual question answering on VizWiz, augmented reality scene understanding, and visual document search on DocVQA, demonstrates that Mode B achieves task accuracy within approximately 5 to 7 percentage points of cloud-only baselines while reducing cloud token cost by over 60 percent and achieving meaningful reductions in membership-inference attack success. A learned adaptive router outperforms confidence-threshold cascade baselines on cost-accuracy Pareto frontiers. PerceptionGuard is implemented as open-source Android and iOS libraries and contributes design heuristics for practitioners building privacy-respecting multimodal mobile applications at scale.